Experimental investigation of Fracture in rubber pad forming of bipolar plate's micro channels. (2017) - Ghadikolaee, Hossein Talebi; Elyasi, Majid; Khatir, Farzad Ahmadi; Hosseinzadeh, Morteza
Abstract: Metallic bipolar plates are the most important part of proton exchange membrane fuel cell (PEMFC). In order to manufacturing of these plates, various method such as Hydroforming, electromagnet forming and stamping have been used. In this study rubber pad forming process was selected in order to forming metallic bipolar plates with stainless steel 316. At first effect of punch load, thickness and hardness of rubber on channel depth (before fracture) were investigated in order to determinate the maximum channel depth before fracture. After that, a novel method was developed by machining the rubber pad in order to prevent from fracture and increase in channel depth. According to the result, increase in hardness of rubber lead to decrease in channel depth and increase in applied force and thickness of rubber lead to increase in channel depth. Maximum filling percentage (before fracture) in rubber pad forming process was 76% achieved by Shore A 40 rubber pad with thickness of 30 mm and maximum thinning percentage before fracture is about 30%. Using new method was successful to prevent from fracture and formability has been increased by machining the rubber pad. As a result, the filling percentage for bipolar plate increased to 88%.